Karl Barth"s epistemology: A critical appraisal - Veldsman, Daniël P. (HTS teologiese studies, 2007)
Can the great 20th century systematic theologian Karl Barth justify the fundamental beliefs he holds regarding the priority of God’s revelation in Jesus Christ as put forward in his impressive and comprehensive Kirchliche Dogmatik? Is it enough and thus theologically justifiable to simply state in the words of Barth that the best theology would need no advocates: it would prove itself? In my appraisal of Barth’s epistemological stance, I would like to argue in this article that his stance in the first place, does not only lead to a total isolation of theological reflection, but secondly through his highly exclusive claim, takes on the character of a personal religious credo expanded into a comprehensive doctrine beyond any form of control, and ultimately thirdly, becomes methodologically in essence a specifically Barthian theology from below. Wenn die Theologie sich eine Wissenschaft nennen lässt oder selber nennt, so kann sie damit keinerlei Verpflictung übernehmen, sich an den für andere Wissenschaften gültigen Massstäbem messen zu lassen. (Karl Barth 1947:8)